Princess Mia - Cabot, Meg. (New York : Harper Teen, 2008)
Princess Mia, struggling to come to terms with her recent breakup with Michael and prepare for an important speaking engagement at a gala for Domina Rei, finds solace and guidance in the diary of a teenage princess for Genovia, and discovers a secret that may change her country's history forever.
Young Adult.
Young Adult
Keywords: Diaries -- Juvenile fiction; High schools -- Juvenile fiction; Princesses -- Juvenile fiction; Self-confidence -- Juvenile fiction; Diaries -- Fiction; High schools -- Fiction; Princesses -- Fiction; Schools -- Fiction; Self-confidence -- Fiction; Diaries -- Fiction; High schools -- Fiction; Princesses -- Fiction; School stories; Self-confidence -- Fiction; New York (N.Y.) -- Juvenile fiction; New York (N.Y.) -- Fiction; New York (N.Y.) -- Fiction